COMPARISON BETWEEN THE DISCOVERY LEARNING MODEL BASED LEARNING AND PROBLEM BASED LEARNING USING SCIENTIFIC APPROACH - . Syarifuddin (Universitas Negeri Makassar, 2017)
This study aimed to compare the mathematics learning outcomes eighth grade students of SMP Negeri 5 Pallangga Gowa taught through Discovery Learning Based Learning and Problem Based Learning Using Scientific Approach to the material opportunities. This type of research is a research experiment. The subjects were students of class VIII.A and VIII.B SMP Negeri 5 Pallangga Gowa in the second semester of the 2014/2015 school year numbered 80 people consisting of 40 people in each group. Data collected consist of data of student learning outcomes and student response data to the device and learning. Data were analyzed using descriptive and inferential analysis. Descriptive Research data show learning outcomes of students who are taught by the teaching model of Discovery-based learning using a scientific approach is at the high category with an average of 82.42 with a standard deviation of 6.09 from the ideal score of 100. The average value of gain 0.75 with a standard deviation of 0.06 of an ideal score of 1 at the high category, and learning outcomes classical completeness of 87.5%, while the response is in the category of students with more positive with an average of 3.29. Learning outcomes of students taught by teaching model Problem-based learning using a scientific approach at the high category with an average of 87.00 with a standard deviation of 7.06 from the ideal score of 100. The average value gain of 0.82 with a standard deviation 0.07 of an ideal score of 1 at the high category, and classical completeness learning outcomes by 95%, while the response is in the category of students with more positive with an average of 3.48. Descriptive mastery learning outcomes and student response is different. Testing the hypothesis of the differences in the results of learning is done by using independent test samples t test with SPSS 20 for significant learning outcomes with a value of α = 0.05 and for normalized gain significant value to the value of α = 0.05. It can be concluded there is a difference in response and student learning outcomes are taught through discovery learning model based learning and problem based learning model study using a scientific approach in class VIII SMP Negeri 5 Pallangga